Alan Saville - Ralston, Ian; Cowie, Trevor (Proceedings of the Society of Antiquaries of Scotland, 2016)
Alan Saville, the archaeologist and prehistorian and a former President of the Society of Antiquaries of Scotland, died in his adopted city of Edinburgh at the age of 69, following a long illness.